Control and filtering of wide-band noise driven linear systems - Bashirov, Gregory S. (My University, 1993)
[Abstract Not Available]
Keywords: Computational methods; Control system analysis; Kalman filtering; Mathematical models; Numerical methods; Optimal control systems; Parameter estimation; Random processes; Stochastic control systems; White noise; Real noise; Separation principle; White noise driven systems; Wideband noise; Wideband noise driven linear systems; Linear control systems